2022
DOI: 10.1093/genetics/iyac129
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of human RNA binding motif protein 48 (RBM48) reveals an essential role in U12-type intron splicing

Abstract: U12-type or minor introns are found in most multicellular eukaryotes and constitute ∼0.5% of all introns in species with a minor spliceosome. Although the biological significance for evolutionary conservation of U12-type introns is debated, mutations disrupting U12 splicing cause developmental defects in both plants and animals. In human hematopoietic stem cells, U12 splicing defects disrupt proper differentiation of myeloid lineages and are associated with myelodysplastic syndrome (MDS), predisposing individu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 68 publications
(94 reference statements)
0
5
0
Order By: Relevance
“…These include NTC complex proteins (PRPF19, SPF27 and SYF1), NTR complex proteins (BUD31 and RBM22), SF3a complex, and phosphoprotein isomerases (PPIL1 and CypE). Conversely, the minor B act complex contains four unique proteins RBM48, ARMC7, SCNM1 and CRIPT that are not present in the major B act complex ( 8 , 30 , 31 ). At least a subset of these differences in protein composition can be explained by the presence of distinct snRNA components in the two spliceosomes which influences the availability of the specific RNA elements for the binding of protein factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include NTC complex proteins (PRPF19, SPF27 and SYF1), NTR complex proteins (BUD31 and RBM22), SF3a complex, and phosphoprotein isomerases (PPIL1 and CypE). Conversely, the minor B act complex contains four unique proteins RBM48, ARMC7, SCNM1 and CRIPT that are not present in the major B act complex ( 8 , 30 , 31 ). At least a subset of these differences in protein composition can be explained by the presence of distinct snRNA components in the two spliceosomes which influences the availability of the specific RNA elements for the binding of protein factors.…”
Section: Discussionmentioning
confidence: 99%
“…The notion that specific protein components of the minor spliceosome are needed only during the intron recognition phase and not in the later assembly steps has been challenged only very recently. The first such factor, the plant ortholog of RBM48, was originally identified as a U12-type intron splicing factor from a transposon screen in maize ( 30 ), and its specificity for U12-type introns was later confirmed in human cells ( 31 ). A cryo-EM structure of the catalytically activated minor spliceosome (B act complex) revealed that RBM48, together with additional three unique proteins ARMC7, SCNM1 and CRIPT, are all specific components of the B act complex ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…These include NTC complex proteins (PRPF19, SPF27 and SYF1), NTR complex proteins (BUD31 and RBM22), SF3a complex, and phosphoprotein isomerases (PPIL1 and CypE). Conversely, the minor B act complex contains four unique proteins RBM48, ARMC7, SCNM1 and CRIPT that are not present in the major B act complex (Bai et al ., 2019; Bai et al ., 2021; Siebert et al ., 2022). At least a subset of these differences in protein composition can be explained by divergent snRNA components between the spliceosomes which change the RNA elements available for the binding of protein factors.…”
Section: Discussionmentioning
confidence: 99%
“…The notion that specific protein components of the minor spliceosome are needed only during the intron recognition phase and not in the later assembly steps has been challenged only very recently. The first such factor, the plant ortholog of RBM48 was originally identified as a U12-type intron splicing factor from a transposon screen in maize (Bai et al, 2019), and its specificity for U12-type introns was later confirmed in human cells (Siebert et al, 2022). A cryo-EM structure of the catalytically activated minor spliceosome (B act complex) revealed that RBM48, together with additional three unique proteins ARMC7, SCNM1 and CRIPT, are all specific components of the B act complex (Bai et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The N-terminus of SCNM1 also functions to stabilize U6atac and RNF113A at the 5′SS, maintenance of which is required for spliceosome activation in vivo ( Incorvaia and Padgett, 1998 ; Bai et al, 2021 ). Structural insights were also important in identifying the novel minor spliceosome protein, RBM48, which is now known to bind ARMC7 and interact with terminal ends of U6atac snRNA via conserved RNA binding residues ( Bai et al, 2021 ; Siebert et al, 2022 ). Structural analyses of the minor spliceosome are a recent advancement and do not yet cover all phases of splicing, notably excluding the U11/U12 di-snRNP.…”
Section: Classification and Splicing Of Intronsmentioning
confidence: 99%